Benefits of Hemicraniectomy Seen Many Years After Malignant Stroke in a Young Patient - Mittal, Anupam; Mittal, Geetanjli; Partikian, Arthur; Liebeskind, David S.; Sanossian, Nerses (Frontiers in Neurology, 2012)
The benefits of hemicraniectomy for malignant middle cerebral artery (MCA) stroke may not be apparent in the 3 to 6 months in which final outcomes are assessed in research studies. We present the case of a 15 year-old who underwent hemicraniectomy for malignant MCA stroke and was significantly disabled 3 and 6 months after event. Over the long-term she was able to graduate from university, play tennis, and live an independent life. Although functional independence with only minor disability is relatively rare in adult hemicraniectomy patients, this outcome may be more easily achieved in children during a longer period of follow-up.